Due Position to Legal Documents under the Hand in Notary Legalization - Nur Amanah Amanah; Achmad Sulchan; Jawade Hafidz (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to investigate and analyze: 1) the position of the deed under hand on legalization by notary and 2) Due to legal documents under the hand that has been in Legalization by Notary. Based on the wording of Article 15 paragraph (2) a and b of Law No. 2 of 2014 on the Amendment of Act No. 30 of 2004 concerning Notary, the Notary in carrying out his authority to conduct the legalization of the deed under the hand. The method used in this study is a socio-juridical. The data in this study are primary data obtained from the field by means of interviews and secondary data consists of primary legal materials, secondary legal materials as well as materials law tertiary literature. Data were then analyzed qualitatively.Based on the analysis, it can be seen that: 1). Position deed under the hand that was authorized by the Notary: when both parties recognize and explain correctly what is in deed under the hand, then the deed under the hand of a criminal offense and be perfect evidence as authentic deed. 2). The legal consequences deed under the hand which has been legalized by Notary: deed under hand on legalization by notary is not a legal effect of evidence which was perfect because they can be disputed later in court, and if the parties deny the strength of evidence in the hands of the judge's decision.Keywords: Deed Under Hand; Notary; Legalization.